Lp-PLA2 Inhibition-The Atherosclerosis Panacea? - Mahir Karakas; Wolfgang Koenig (MDPI AG, 2010)
Based on the complex pathophysiology of atherosclerosis, a large number of biomarkers that relate to lipids, inflammation, immunity, thrombosis and hemostasis, have been investigated experimentally, in epidemiologic studies and in clinical trials. Interest focuses on their potential role to aid in risk stratification, as possible surrogate markers of atherosclerosis, and potential targets for therapy. More recently, one lipid associated biomarker, lipoprotein-associated phospholipase A2 (Lp-PLA2), has gained considerable interest. In addition to a plausible pathophysiological role by generating pro-inflammatory and pro-atherogenic compounds from oxidized LDL in the vessel wall, there is a large, fairly consistent epidemiological database indicating that increased levels of Lp-PLA2 mass or activity are associated with increased risk for cardiovascular outcomes; such data further suggest that it might improve risk stratification. In addition, clinical studies indicate that increased Lp-PLA2 levels are associated with endothelial dysfunction. Moreover, it may also serve as an interesting therapeutic target, since a specific inhibitor of the enzyme is available with promising animal data and initial positive data in humans. Recent experimental data from a hyperlipidemic diabetic pig model strongly suggest that increased Lp-PLA2 in the vessel wall is associated with a more vulnerable plaque phenotype which can be modulated by inhibiting Lp-PLA2 activity. A biomarker study in more than 1,000 patients with CHD over three months has demonstrated a positive effect on various inflammatory molecules. In addition, an imaging study using IVUS based modalities (greyscale, virtual histology, and palpography) together with a panel of biomarkers (IBIS-2) has been done in more than 300 patients with CHD treated over 12 months and results indicate that the progression of the necrotic core of the plaque can be retarded. Inhibition of the pro-atherogenic and pro-inflammatory effects of Lp-PLA2 may therefore contribute to decrease the residual risk in high risk patients already on polypharmacotherapy. This hypothesis is now being tested in two large phase 3 clinical trials. Thus, Lp-PLA2 indeed may represent a biomarker and a promising target for intervention.